Edukasi Mitigasi Bencana Guna Peningkatan Literasi Gempa Bumi dan Tsunami Berbantuan E-Modul Terintegrasi Augmented Reality pada Siswa MIN 4 Maluku Tengah - Salman Hamja Siombone; Emy Sohilait; Mursaid Dahlan; Calvin Talacua; Gilbert W. Tita; Naldo F. Selumena (LOSARI DIGITAL, 2026)
Earthquake and tsunami mitigation is a strategic effort to minimize the risks, impacts, and losses from disasters through structural and non-structural approaches, including school-based disaster education. Earthquake and tsunami mitigation education activities were carried out at MIN 4 Central Maluku, Tehoru Village, on September 22–27, 2025, involving 28 fourth-grade students as respondents. This community empowerment program was developed using a Participatory Action Research (PAR) approach, integrating learning e-modules with Augmented Reality (AR) media to improve understanding of disaster concepts. Evaluation was carried out using earthquake and tsunami literacy test instruments, communication skills rubrics during in-house training (IHT), and student perception and interest questionnaires. The results showed an increase in disaster literacy, with an average classical N-Gain of 62.04% (a quite effective category). In addition, students' communication skills averaged 87.50 (very good), and the majority responded positively to the use of AR e-modules in disaster mitigation learning.